Peran dan Hubungan Pesantren di Indonesia dengan Madrasah Nizhamiyah: Pendidikan Islam yang Berintegrasi - Winarno, Dwi; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2024)
This research discusses the relationship and evolution of Islamic education through a comparison between Islamic boarding schools in Indonesia and Madrasah Nizhamiyah. Even though they are separated by hundreds of years and different cultural realities, both have a significant impact in shaping the character and knowledge of Muslims. The aim of this research is to explore the continuity of Islamic values and the adaptation of Islamic education carried out by Islamic boarding schools in Indonesia, inspired by the Madrasah Nizhamiyah educational model. The research method used involves comparative analysis between Islamic education approaches in Islamic boarding schools and Madrasah Nizhamiyah. Literature study approach to explore the essence of the values and educational methods applied by these two institutions. The results of the research show that, despite significant contextual differences, Islamic boarding schools in Indonesia still maintain the continuity of Islamic values which are in line with the holistic approach of the Nizhamiyah Abbasid Madrasah. Islamic boarding schools have adopted and adapted educational principles from Madrasah Nizhamiyah, creating harmonization between Islamic traditions and local realities. This research also reveals how Islamic boarding schools in Indonesia have intelligence in combining a universal Islamic education approach with local wisdom. The contextual adaptation carried out by Islamic boarding schools creates an understanding of Islam that is relevant to the dynamics of Indonesian society, without losing the essence of basic Islamic values. This research provides in-depth insight into how Islamic boarding schools in Indonesia build relationships and utilize the intellectual heritage of Madrasah Nizhamiyah. It is hoped that the conclusions of this research can make a significant contribution to the development of Islamic education in Indonesia, as well as stimulate ideas to support dialogue between Islamic educational institutions throughout the world.